Perilaku Picky Eating sebagai Faktor yang Berhubungan dengan Status Gizi Anak Usia Pra-Sekolah - Brivian Florentis Yustanta (Pusat Riset dan Inovasi Nasional, 2024)
Picky eating behavior if it continues will result in a lack of nutritional needs, causing children's growth and development to be disrupted as a result children experience less than optimal nutrition. The purpose of this study was to determine the relationship between picky eating behavior and nutritional status in children aged 36-60 months at Santa Maria Pare Kindergarten, Kediri Regency. The analytic research design uses a cross sectional approach. The independent variable is picky eating behavior and the dependent variable is nutritional status. The population is 95 children with a sample of 76 respondents. The sampling technique used simple randoml sampling. Data collection was carried out on 17 – 22 July 2023 at Santa Maria Pare Kindergarten, Kediri Regency. The research instrument used the CEBQ (Child Eating Behavior Questionnaire) questionnaire and digital scales. Data analysis used the contingency coefficient test. The results showed that 42 children (53.9%) were picky eatings and 39 had a poor nutritional status (51.3%). The contingency coefficient test results ρ = 0.002 <0.05 which indicates H1 is accepted, meaning that there is a very close relationship between picky eating behavior and nutritional status. Picky eating occurs depending on the diet and type of food consumed by the child, if the intake of other energy sources is sufficient to meet their energy and protein needs, thereby protecting the child from decreasing nutritional status and maintaining normal nutrition